Students' Mathematic Problem Solving Ability with Problem Solving Learning Model in Class VII SMP Negeri 2 Singkawang - Ayu Susantri; Nurul Husna; Buyung Buyung (Universitas Maritim Raja Ali Haji, 2022)
Students still need to improve their capacity for solving mathematical puzzles. The study aimed to evaluate how well the Problem-Solving learning model helped students become more adept at solving algebra-related mathematical problems. This study is an illustration of hybrid research (Mixed Methods). Class VIIA served as the experimental class, and Class VIID served as the control class for the study. Test forms, observation forms, and interviews served as instruments. Statistics are used in quantitative data analysis, whereas in qualitative data analysis, data is reduced, presented, and conclusions are drawn. The findings revealed that: (1) Mathematical problem-solving skills were improved in Problem-Solving Learning Model classes compared to classes using the Discovery Learning Model; (2) The Problem-Solving Learning Model defined what was meant by active student participation in class, with the percentage of student activity obtained being 41.12% at the first meeting with the quite active category and 89.74% at the second meeting with the very active category.